Smart Parenting Rooted in Local Wisdom: A Solution to Digital Disruption in Early Childhood - Chantika Bunga Santoso; Adillah Makayla Gusdian Garini; Audra Adelia Muflikhah; Aisyah Maharani (Journal of Art and Creativity in Early Childhood Education, 2026)
The digital transformation brings dual impacts on early childhood parenting practices. On one hand, children are increasingly exposed to technological devices, social media platforms, and various digital content. On the other hand, conventional parenting approaches that rely on face-to-face communication and traditional social values are beginning to face limitations. This paper examines parenting challenges in the digital technology era along with alternative solutions through the concept of smart parenting grounded in local wisdom. This study was conducted by analyzing various forms of parental guidance practices in several communities, including adaptive parenting training programs, smart parenting seminars, and efforts to integrate local cultural values with contemporary parenting approaches. The findings indicate that parents need a proportional parenting approach: optimizing the responsible use of technology through supervision, control, and active accompaniment, while instilling character values, spirituality, and local cultural wisdom as the ethical foundation for children. The smart parenting approach based on local wisdom demonstrates effectiveness in increasing awareness, competence, and active involvement of parents in facing digital era challenges. Therefore, adaptive parenting strategies that integrate technology with noble cultural values can be a strategic solution in shaping an early childhood generation that is not only digitally competent, but also possesses strong character and commendable moral values.